Operative versus nonoperative treatment for displaced midshaft clavicle fractures: a meta-analysis based on current evidence (Clinics, 2015)
Literature searches of the Cochrane Library, PubMed, EMBASE, Web of Science, LILACS, China National Knowledge Infrastructure, and Wanfang Data databases were performed from 1966 to September 2014. Only randomized and quasi-randomized controlled clinical trials comparing operative and nonoperative treatments for displaced midshaft clavicle fractures were included. Data collection and extraction, quality assessment, and data analyses were performed according to the Cochrane standards. Thirteen studies were considered in the meta-analysis. Constant scores and the Disabilities of the Arm, Shoulder and Hand scores were improved in the operative fixation group at a follow up of one year or more. The nonunion and symptomatic malunion rates were significantly lower in the operative group. Additionally, the nonoperative group had a higher likelihood of neurological symptoms compared with the operative group. A significantly higher risk of complications was found in patients treated conservatively than in those who underwent operative fixation. However, when patients with nonunion and symptomatic malunion were excluded from the analysis, no significant differences in the complication rate were found. We concluded that based on the current clinical reports, operative treatment is superior to nonoperative treatment in the management of displaced midshaft clavicle fractures. However, we do not support the routine use of primary operative fixation for all displaced midshaft clavicle fractures in adults.